Pemanfaatan Teknologi Digital Dalam Pembelajaran Pendidikan Agama Kristen Oleh Guru Di UPTD SDN Air Panas - Novita Beri Yalla; Harun Y. Natonis (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2026)
The implementation of the Independent Curriculum demands digital transformation at all levels of education, including elementary schools in rural regions. This study aims to analyze the utilization of digital technology in Christian Religious Education (CRE) learning by teachers at UPTD SDN Air Panas, Pantar Tengah District, Alor Regency, East Nusa Tenggara. This study applied a qualitative method with a descriptive case study approach. Data collection was carried out through classroom observations, in-depth interviews with CRE teachers, and learning documentation. The results showed that teachers at SDN Air Panas utilized digital technology through audio-visual media of Bible stories on YouTube, mobile-based digital Bible applications (YouVersion), and semi-digital collaborative assignments. This utilization proved capable of increasing students' concentration, retention, and active engagement in reflecting on Christian faith values. However, the effectiveness of this integration is still hindered by geographical challenges in the form of unstable internet network constraints and the uneven distribution of school gadget infrastructure. This study recommends the need to strengthen offline-digital strategies and continuous theological-practical assistance for optimizing the quality of CRE in outermost, underdeveloped, and frontier areas.